2018
DOI: 10.1108/ijotb-03-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Integrating video technology and administrative practice in policing

Abstract: Purpose The purpose of this paper is to argue that philosophic and administrative thought have enframed (Heidegger, 1977) us to unconsciously accept technology in public administration and the bureaucracy. Design/methodology/approach It builds on literature in phenomenology. Findings It discusses the implications of this phenomenon for organizational decision-making, management, and governance more broadly. Practical implications It questions whether we should utilize video technology in policing, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Government in the technological age applies and extends utilitarian ideals at the expense of the quality of administrative practice. And thinkers like Herbert Simon have conditioned us to accept technology on the basis of efficiency without thinking critically about some of the consequences (Piccorelli & Elias, ). The proliferation of social media in our public sphere means we think differently about how to listen to citizens; public agencies replace felt sense and judgment with social media‐based measures that narrow our conception of the public.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Government in the technological age applies and extends utilitarian ideals at the expense of the quality of administrative practice. And thinkers like Herbert Simon have conditioned us to accept technology on the basis of efficiency without thinking critically about some of the consequences (Piccorelli & Elias, ). The proliferation of social media in our public sphere means we think differently about how to listen to citizens; public agencies replace felt sense and judgment with social media‐based measures that narrow our conception of the public.…”
Section: Resultsmentioning
confidence: 99%
“…In a desperate attempt to gain public approval, governments adopt new technology, but they rarely assess what any technology means for governance beyond making it more efficient. Instead of being lured by efficiency and the potential to realize utilitarian ideals (Piccorelli & Elias, ), we need to examine their full impact much more closely. In Arendt's terms, we need to think and judge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heidegger (1977) went further to warn that technology does not just change our experience, but actually orders us. This is because we take for granted the enframing power of technology to change how and what we experience, and how we understand the world (Heidegger, 1977, p. 304-6;Piccorelli & Elias, 2018;Piccorelli & Stivers, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With increased surveillance (i.e., cameras fixed to objects and people) the notion of a witness is now being pushed beyond traditional boundaries of those who were physically present. The courts and public increasingly rely on video footage as a form of evidence to be considered alongside eyewitness accounts and, in many cases, ahead of or in place of these accounts (Piccorelli & Elias, 2018). In the police shooting of Tamir Rice, for example, police experts said the expert video analysis provided "reasonable justification" (McGinty, 2015) for the shooting because it "found that Rice's arm moved forward and toward his waist as the police car neared" (Palmer, 2015).…”
Section: Introductionmentioning
confidence: 99%